Prospect theory in the financial decision-making process: An empirical study of two Argentine universities - Rogelio Ladrón de Guevara Cortés; Leticia Eva Tolosa; María Paula Rojo (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This paper aims to provide empirical evidence for using the prospect theory (PT) basic assumptions in the Argentine context. Mainly, this study analysed the financial decision-making process in students of the economic-administrative academic area of two universities, one public and one private, in Córdoba. Design/methodology/approach -The analysis methodology included (1) the descriptive statistical analysis to identify the presence of the certainty, reflection and isolation effects; (2) the construction of a set of indicators on the application of the PT; (3) the chi-squared independence test, to determine if the decisions made are independent of the degree course taken; (4) the non-parametric Kruskal-Wallis test, to determine if the decisions made by individuals vary according to the semesters taken or students' levels of progress; and (5) the non-parametric Mann-Whitney test, to determine if there are differences between the decisions made by men and women. Findings - The empirical results provided evidence on the effects of certainty, reflection and isolation in both universities, concluding that the study participants make financial decisions in situations of uncertainty based more on PT than on expected utility theory. Originality/value - This study contributes to the empirical evidence in a different Latin-American context, confirming that individuals make financial decisions based on the PT independently of their degree course, semester, level of advance, gender or the kind of university where they belong (public or private).
Keywords: D18; G11; G41; J16; 330; Prospect theory; Behavioural finance; Financial decisions; Rationality and risk; Non-parametrictests; Córdoba; Argentina